The oppression of women in the novels of Sembene Ousmane and Tsitsi Dangarembga - Mphiko, Benjamin Lesibana (University of Limpopo, 2016)
The primary aim of this study is to examine the oppression and repression of African women through the collusion of indigenous African patriarchy and colonial, imperialist values. The selected novels are Nervous Conditions (1988) and God’s Bits of Wood (1960) by Tsitsi Dangarembga and Sembene Ousmane, respectively. The study focuses on the roles played by both African and European values in the class, gender and racial oppression of African women. Using the theoretical frameworks of Marxism and Feminism, the study evaluates issues of women’s oppression, repression and marginalisation. The selected literary texts are closely analysed with a view to exploring and establishing the nature and form of African women’s multiple oppressions through the connivance between African patriarchy and European colonial hegemonic norms. Lastly, the study aims to contribute to the existing body of knowledge on the topical issue of African women’s oppression. Keywords: Colonial values; African patriarchy; Hegemonic norms; Oppression; Oppression; Marginalisation; Collaboration; Women and the girl child
Thesis (M. A.(English Studies)) --University of Limpopo, 2016
Keywords: Colonial values; African patriarchy; Hegemonic norms; Oppression; Oppression; Marginalisation; Collaboration; Women and the girl child; Sex discrimination against women; Sex discrimination in employment